Initial Result of Body Earthing on Student Stress Performance - Mahfuzah, Mustafa; Sia, KeeHuong; Norizam, Sulaiman; Rosdiyana, Samad; Nor Rul Hasma, Abdullah; Nasrul Salim, Pakheri; Mohd Nasir, Taib (2015)
The body earthing technique is a kind of method that can neutralize our positive charge and negative charge in our body by connecting to the earth. It is believed that body earthing gives a positive effect on human body. There is a possibility that EEG signals can verify the positive effect of body earthing. The experiment of body earthing is done by attaching the patched kit to the hand of the subjects. Then, low voltage of multimeter was used to measure the body voltage of the subjects and EEG signals were collected. After that, the collected EEG data were processed by Band-pass filter in MATLAB to filter out the Alpha and Beta frequency bands separately. The threshold of signal amplitude was set to -100 µV to 100 µV in order to remove the noise of the signals. Next, the Power Spectral Density (PSD) graphs of each EEG signals were plotted and the maximum points of each signal were recorded. Then the peak points were plotted in a histogram to see the changes of the Alpha and Beta band signals. Lastly, the results of before the body earthed and after body earthed were compared through the histogram plotted. It is observed that, before the body earthed, the Alphaband is low, while the Beta-band is high. Then after body earthed, the Alpha band increased, while the Beta band are decreased.